Vehicle Routing by Heuristic Method : A Case Study of Private Company (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research was to 1) study the best route routing method, 2) compare the route routing by heuristic method and saving algorithm, and 3) reduce fuel cost and unnecessary cost. By comparing the distance of the route using heuristic method and saving algorithm and comparing the fuel table. It was found that the calculation of the transportation route by heuristic value has a total distance of all 5 routes of 908.3 kilometers. While the calculation of the transportation route by Saving algorithm has a total distance of all 5 routes of 928.6 kilometers. Therefore, the calculation of the transportation route by heuristic value has a distance of less than 20.3 kilometers and the fuel volume of the transportation route by heuristic value has a total fuel volume of all 5 routes of 299.54 liters per day. While the calculation of the transportation route by Saving algorithm has a fuel volume of all 5 routes of 330.67 liters per day. Therefore, the calculation of the transportation route by heuristic value the amount of fuel used in the transport route is less than 31.13 liters/day. Therefore, the application of this heuristic method is suitable for operators whose transportation characteristics are in accordance with the conditions, have travel time as specified by law, and have a clear service time frame. However, the fuel consumption and transportation time cannot be accurately predicted because the overall traffic conditions and weather conditions of each day are not the same. Therefore, the fuel consumption and travel time may deviate slightly from the original.